2021
DOI: 10.1002/cbic.202100534
|View full text |Cite
|
Sign up to set email alerts
|

The Small Open Reading Frame‐Encoded Peptides: Advances in Methodologies and Functional Studies

Abstract: Small open reading frames (sORFs) are an important class of genes with less than 100 codons. They were historically annotated as noncoding or even junk sequences. In recent years, accumulating evidence suggests that sORFs could encode a considerable number of polypeptides, many of which play important roles in both physiology and disease pathology. However, it has been technically challenging to directly detect sORF‐encoded peptides (SEPs). Here, we discuss the latest advances in methodologies for identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 173 publications
(272 reference statements)
0
7
0
Order By: Relevance
“…It turned out that only four of these proteins were folded and one protein was partially folded, whereas the majority of proteins were in the molten globule state, were totally unfolded, or could not be produced. Various reviews summarize the specific challenges in the heterologous or homologous production of μ-proteins, in contrast to average-sized proteins ( Storz et al, 2014 ; Orr et al, 2020 ; Cassidy et al, 2021 ; Steinberg and Koch, 2021 ; Tharakan and Sawa, 2021 ; Chen et al, 2022 ; Gray et al, 2022 ; Leong et al, 2022 ; Schlesinger and Elsässer, 2022 ; Weidenbach et al, 2022 ; Zhang et al, 2022 ; Dong et al, 2023 ; Hassel et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It turned out that only four of these proteins were folded and one protein was partially folded, whereas the majority of proteins were in the molten globule state, were totally unfolded, or could not be produced. Various reviews summarize the specific challenges in the heterologous or homologous production of μ-proteins, in contrast to average-sized proteins ( Storz et al, 2014 ; Orr et al, 2020 ; Cassidy et al, 2021 ; Steinberg and Koch, 2021 ; Tharakan and Sawa, 2021 ; Chen et al, 2022 ; Gray et al, 2022 ; Leong et al, 2022 ; Schlesinger and Elsässer, 2022 ; Weidenbach et al, 2022 ; Zhang et al, 2022 ; Dong et al, 2023 ; Hassel et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notable advancements encompass the establishment of ribosome profiling methods, advances in mass spectrometry (peptidomics), and enhancements in gene/ORF prediction through bioinformatics refinements. Several recent reviews summarize current knowledge about very small proteins in archaea, bacteria, and eukaryotes ( Storz et al, 2014 ; Orr et al, 2020 ; Cassidy et al, 2021 ; Steinberg and Koch, 2021 ; Tharakan and Sawa, 2021 ; Chen et al, 2022 ; Gray et al, 2022 ; Leong et al, 2022 ; Schlesinger and Elsässer, 2022 ; Weidenbach et al, 2022 ; Zhang et al, 2022 ; Dong et al, 2023 ; Hassel et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…C8-SPE is another method based on hydrophilic and hydrophobic properties of SEPs [ 66 ]. It was reported that a combination of these methods may be able to identify more SEPs [ 71 ].…”
Section: Peptidomic-based Methodology For Identification Of Sepsmentioning
confidence: 99%
“…Therefore, a small portion of smORFs have the potential to be translated into polypeptides ( Wu et al, 2019 ; Ladoukakis et al, 2011 ). These peptides with lengths less than 100 amino acids are called micro-peptides or smORF-encoded peptides (SEPs) ( Chen et al, 2021 ). Further studies on micro-peptides based on bioinformatics and high-throughput sequencing technology have found that micro-peptides not only are highly conserved throughout evolution ( Ladoukakis et al, 2011 ) but also play an important regulatory role in a series of processes such as biological development ( Sanchez-Ortiz, 2017 ; Read et al, 2019 ), metabolism ( Makarewich et al, 2018 ; Stein et al, 2018 ), and cancer incidence ( Pang et al, 2020 ; Wu et al, 2020 ; Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%